A Cross‐National Analysis of Party Switching. Issue 1 (17th January 2013) - O'brien, Diana Z.; Shomer, Yael
<x xml:space="preserve">Abstract</x> Though instances of party switching have been widely documented, there is little cross‐national research on this phenomenon. The prevalence of switching is therefore unknown, and the factors influencing this behavior remain unclear. Using the most comprehensive dataset on party switching ever constructed, we illustrate both that interparty movement is more common than previously assumed and that there are substantial differences in its prevalence across parties. To explain this variation, we examine the relationship between legislators' motivations, institutional arrangements, and switching. We find that motivational explanations are correlated with interparty movement and that institutional arrangements exhibit only limited direct influence on switching.